The interplay of economic shocks and cultural practices in child marriage: Comparative evidence from India and Zambia during the COVID-19 pandemic - Pascal Mohamed Mounchid; Shruti Shukla; Janina Isabel Steinert (PLoS ONE, 2026)
Child marriage is a critical issue in many low- and middle-income countries (LMICs), further exacerbated by the COVID-19 pandemic due to economic instability. This study examines the impact of the pandemic on child marriage rates in India and Zambia, focusing specifically on socio-cultural and economic influences. We collected quantitative and qualitative data from adolescent girls aged 13–18 years in India ( n = 3,049) and 15–19 years in Zambia ( n = 1,615) between February and September 2022. Multi-variable linear probability regression analyses were applied to assess the pandemic’s effect on child marriage and how it was affected by cultural marriage practices of bride price (Zambia) and dowry (India). While we found no significant increase related to pandemic-induced economic strains in Zambia, we observed a significant increase in child marriage rates related to the pandemic circumstances in India. In-depth analysis of qualitative data indicated that reduced dowry demands and lower wedding costs, resulting from restrictions on guest numbers, drove families to prepone weddings and marry off their daughters during the pandemic. Our findings suggest that economic or health shocks affect child marriage practices differently based on local socio-cultural context.